Pakistan and Ali Bhutto (Friends of Pakistan, 1978)
On the conviction of Zulfikar Ali Bhutto, b. 1928, former prime minister of Pakistan for the alleged murder of Nawab Mohammed Ahmed Khan on 1 November 1974; compilation of court proceedings, statements, newspaper reports, etc.